Introduction to stellar astrophysics - Böhm-Vitense, E. (Cambridge University Press, 1989)
This comprehensive textbook conveys the basic physical ideas and laws used in the study of the outer layers of a star. The stellar atmosphere emits the light which we see. The only layers of a star where we can get direct information about temperature, pressure and composition are in the atmosphere. This complete account first introduces stellar magnitudes, spectra and temperatures. This is followed by a full discussion of radiative transfer in a stellar atmosphere, which leads to descriptions of line formation, the spectrum of hydrogen, and spectral analysis. Finally the structural components that are accessible, such as the convestion zone, chromosphere, corona, and mass outflow are described. The book will interest any student with a knowledge of physics and mathematics who needs to learn about stellar atmospheres.